Fabrication of Coconut Shell-Derived Graphitic Activated Carbon for Carbon-based Electrode Materials - Irma Fifa Yanti; Pratama Jujur Wibawa; Aris Mukimin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
This study aims to convert low-value plantation biomass waste into high-value materials. The process involves transforming coconut shell charcoal (CSC) into activated carbon and subsequently producing coconut shell graphitic-like activated carbon (CSGAC). Using a thermal graphitization method with a FeCl3 catalyst at 900°C for 1 hour in a nitrogen atmosphere, graphite microstructures (CSGAC) were formed on the coconut shell activated carbon (CSAC) framework. XRD, FTIR, SEM, and BET analyses confirmed the successful formation of CSGAC. The electrical conductivity of CSGAC, measured at 148 µS, highlights its potential as a cost-effective, renewable, and environmentally friendly raw material for carbon-based electrodes.